Turkish Political Market and the Perception of Political Parties - Cihat Polat (Tržište, 2015)
This study attempts to describe the Turkish political market and determine where and how Turkish political parties are perceived by voters. The study uses a two-dimensional map to determine the voter perceptions of the parties in the Turkish political market based on a survey questionnaire applied to 400 young voters. It also investigates whether there are any major differences in the perception of parties in the political space based on voter ideologies. The study finds that young voters have clear perceptions of the positions of Turkish parties. It also finds that voter perceptions of parties vary based on voters’ ideological positions.